Modelling the characteristics of a 6/4 Switched Reluctance Motor using neural network / Mohamed Azmi Mohamed Razali - Mohamed Razali, Mohamed Azmi (1997)
Switched Reluctance Motor (SRM) are almost always operated within the saturation region and therefore has a very large operation region. This yields very strong nonlinearities, which makes it difficult to derive a comprehensive mathematical model for the behaviour of the machine. Neural Networks can be used to overcome such problems. This paper presents Neural Networks as a tool to model the characteristics of the motor. The flux-linkage versus current relationship as a function of rotor position for a 6/4 SRM was modelled using Neural